1993
DOI: 10.1364/ao.32.001677
|View full text |Cite
|
Sign up to set email alerts
|

Space optics: an introduction by the editors

Abstract: This feature of Applied Optics consists of papers on the Hubble Space Telescope and its instruments as well as other new instruments and other new optics technology for space science. Many of the papers are an outgrowth of the papers presented at the Second Space Optics Topical Meeting, October 1991, in Williamsburg, Va. This introduction provides an overview for the papers related to the Hubble Space Telescope: measurement of the error and approaches to correct for the error.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The early severe aberrations of HST's optical system were an important driver of phase-retrieval algorithms. Several efforts to characterise HST were published in an Applied Optics special issue (Breckinridge and Wood, 1993). Solving the phase-retrieval problem provides a reliable approach to characterise the optical system accurately.…”
Section: Parametric Psf Modelsmentioning
confidence: 99%
“…The early severe aberrations of HST's optical system were an important driver of phase-retrieval algorithms. Several efforts to characterise HST were published in an Applied Optics special issue (Breckinridge and Wood, 1993). Solving the phase-retrieval problem provides a reliable approach to characterise the optical system accurately.…”
Section: Parametric Psf Modelsmentioning
confidence: 99%
“…The Jet Propulsion Laboratory Wide-Field and Planetary Camera 2 (JPL WFIPC-2) has a pupil close to the 1-cm diameter secondary mirror where the correction for the HST primary mirror error was successfully placed. 3 Meinel and Meinel4 showed that the correction factor was related to the ratio of the primary mirror diameter to the exit pupil diameter. This means that the stable errors of an inflatable mirror can be corrected by a small element whose diameter is set by the required wavefront error (WFE) reduction factor.…”
Section: Upgrading To Visible Passband Requirementsmentioning
confidence: 99%